Speech text of the 6th ISM international statistical conference (ISM-6 2023) / Prof. Datuk Ts. Dr. Roziah Mohd Janor - Mohd Janor, Roziah (2023)
I would like to extend a warm welcome to our distinguished local and international speakers, participants, and guests to the 6th ISM International Statistical Conference (ISM-6 2023), hosted by Universiti Teknologi MARA (UiTM) and co-organised by the Malaysian Institute of Statistics (ISMy)